Analisis Pembentukan MAT Pada Jaringan Sederhana Menggunakan Program Lazarus - Handayani, Esty; Sulistyorini, Rahayu; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Origin Destination Matrix (O-D MATRIX) is two- dimensional matrix are often to described the patterns of movement that contains information the amount of intrazone movement. O-D MATRIX formation in this research on simple network with 5 origin-destination zone (O-D) used Gravity method with two-limitation . In this research, O-D MATRIX formation on a simple network using Lazarus program. Lazarus is the one of Integrated Development Environment (IDE) from Free Pascal Compailer (FPC). FPC that can be used for Window, Linux, and MAC. If the previous calculations requier a longer time, this program will be quickly and efficiently of O-D Matrix. It takes 3 hours to calculate O-D Matrix manualy and input the formula will enhance error possibility. This program spents 5 minutes to calculate O-D Matrix . Keywords: Lazarus, Origin Destination Matrix, Zone